Prevalence of Chlamydia trachomatis infection in homosexual men. Issue 3 (June 1987) - Sulaiman, M Z; Foster, J; Pugh, S F
Abstract : Chlamydial cell culture isolation rates from 51 unselected homosexual men were 9.3% from the urethra, 4.3% (pharynx), and 6.5% (rectum). All the positive cultures showed extremely few inclusions. Direct immunofluorescence with the Microtrak reagent (Syva) was an acceptable alternative technique for non-genital sites, whereas the infectious disease enzyme immunoassay (IDEIA) (Boots-Celltech) was unsuitable.